Reprogramming of human urine cells into cardiomyocytes via a small molecule cocktail in xeno-free conditions - Yu Chen; Aoli Li; Aijie Liu; Wei Zheng; Haishi Fan; Jingwei Zhang; Chenwen Huang (Communications Medicine)
Abstract Background Cell therapy, particularly using cardiomyocytes, shows significant promise for treating heart failure. Direct reprogramming of somatic cells into cardiomyocytes using small molecules is advantageous due to its efficiency and cost-effectiveness. Methods Human urine-derived cells (hUCs) were transdifferentiated into functional cardiomyocyte-like cells (hCiCMs) using a cocktail of 15 small molecules under xeno-free conditions. Various Characterizations were performed, including immunofluorescence, transmission electron microscopy (TEM), qPCR, single-cell RNA sequencing, patch-clamp recordings, and intracellular Ca²+ measurements. The therapeutic potential was tested in both mouse and porcine models of myocardial infarction (MI). Results Reprogramming efficiency achieves 15.08% on day 30, with purity reaching 96.67% on day 60. hCiCMs display cardiomyocyte markers, sarcomeric structures, and abundant mitochondria. Electrophysiological analysis confirms ventricular-like action potentials and regular calcium transients. Single-cell RNA sequencing reveals cardiomyocyte subpopulations resembling 13-week embryonic human heart cells, with gene ontology analysis indicating successful maturation. In the MI model, hCiCM transplantation improves cardiac function, increasing ejection fraction and fractional shortening while reducing fibrosis. Conclusions This study demonstrates the successful reprogramming of hUCs into functional hCiCMs using small molecules under xeno-free conditions, offering a scalable, autologous cell source for cardiac repair with significant potential for regenerative therapies.